Resilience in health workers of a pediatric intensive care unit (Revista Venezolana de Salud Pública, 2019)
Health professionals are subject to stressful situations almost daily, the current Venezuelan reality means that thesesituations are not limited only to the workplace but even to the daily life of all citizens; In this sense, the successfulresolution of these situations will depend on the subject's own resilience, which will help reduce stress, improvephysical and mental well-being and therefore the quality of service provided. Distribute the professionals according tosocial-labor variables; Determine the levels of resilience. A quantitative, correlational, non-experimental research wascarried out. The population was constituted by the health personnel that worked in the PICU and the sample by 33workers who met the inclusion criteria: more than 6 months working in the PICU. The average age was 38.6 years.More than 80% was female. The highest proportion was married (45.5%) and was from the nursing area (60.6%). Morethan 90% had at least more than 2 years of seniority. 45.5% presented average levels of resilience